2007
DOI: 10.1152/ajprenal.00101.2007
|View full text |Cite
|
Sign up to set email alerts
|

Fractional urinary excretion of endothelin-1 is reduced by acute ETB receptor blockade

Abstract: Goddard J, Johnston NR, Cumming AD, Webb DJ. Fractional urinary excretion of endothelin-1 is reduced by acute ETB receptor blockade. Am J Physiol Renal Physiol 293: F1433-F1438, 2007. First published September 12, 2007; doi:10.1152/ajprenal.00101.2007.-Evidence suggests that urinary excretion of endothelin-1 (ET-1) reflects renal ET-1 production and is independent of systemic ET-1 activity. The influence of ET receptors on urinary ET-1 excretion has not been studied in humans, yet peritubular ETB receptors are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…Moreover, fractional excretion of ET-1, TGF-␤, and LCN2-NGAL was not significantly correlated with their serum levels or eGFR (data not shown). Collectively, these data suggest that the amount of ET-1, TGF-␤, and LCN2-NGAL filtered at the glomerulus contributed relatively little to the amount present in the urine, as previously reported in patients with chronic kidney disease (7,23).…”
Section: Identification Of Differentially Expressed Genes In Db/db Kisupporting
confidence: 80%
“…Moreover, fractional excretion of ET-1, TGF-␤, and LCN2-NGAL was not significantly correlated with their serum levels or eGFR (data not shown). Collectively, these data suggest that the amount of ET-1, TGF-␤, and LCN2-NGAL filtered at the glomerulus contributed relatively little to the amount present in the urine, as previously reported in patients with chronic kidney disease (7,23).…”
Section: Identification Of Differentially Expressed Genes In Db/db Kisupporting
confidence: 80%
“…First, as renal function declines, plasma ET-1 levels increase. 52,53 It remains unclear whether the rise in plasma ET-1 in chronic kidney disease (CKD) is because of biologically active or simply immunologically competent peptide, but infusion of exogenous ET-1 to bilaterally nephrectomized rats results in a increased plasma half-life of ET-1 and a prolonged rise in BP compared with shamoperated rats 54 consistent with the idea that elevated plasma ET-1 concentrations in CKD may contribute to hypertension. Second, there is an upregulation of renal ET-1 production in CKD, 55 as reflected by increased urinary ET-1 excretion.…”
Section: Hypertension Associated With Chronic Kidney Diseasementioning
confidence: 85%
“…Second, there is an upregulation of renal ET-1 production in CKD, 55 as reflected by increased urinary ET-1 excretion. 53,56 The effects of exogenous ET-1 on the renal vasculature are vasoconstriction, activating the renin-angiotensin-aldosterone system, and causing salt and water retention, both of which have the potential to raise BP. Animal data suggest that, in CKD, the renal vasculature may be more sensitive to the vasoconstrictor effects of ET-1 than in normal kidneys.…”
Section: Hypertension Associated With Chronic Kidney Diseasementioning
confidence: 99%
“…Although plasma ET-1 levels are not a reliable measure of vascular ET-1 production, owing to its predominantly abluminal release (40), urinary ET-1 excretion is independent of plasma ET-1 concentrations (13,31) and is well-correlated with renal ET-1 production (4,38). A few small studies showed a rise in plasma (20) and urine (26) ET-1 in severe CKD, and our group previously demonstrated increases in plasma and urinary ET-1 concentrations in eight subjects with noninflammatory renal disease, across a range of glomerular filtration rates (GFR) (13). However, there are no data on how renal inflammation may alter these profiles and hence on the utility of urinary ET-1 as a potential biomarker of renal inflammation.…”
mentioning
confidence: 99%